Shape memory esophageal stent with anti-displacement function and preparation method thereof
By adopting a double-layer structure shape memory esophageal stent, using a functional three-arm polylactic acid support layer and a multifunctional tissue adhesion layer, the biodegradability, anti-displacement ability and matching degree with human tissues are achieved, and the problems of poor biodegradability and rigidity mismatch of existing stent materials are solved.
Patent Information
- Application Number
- CN202411992218.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing esophageal stent materials have poor biodegradability and their rigidity does not match human tissue, resulting in a high displacement rate and is difficult to meet clinical needs.
Using a double-layer structured shape memory esophageal scaffold, the support layer is constructed from a functionalized three-arm polylactic acid skeleton, and the tissue adhesion functional layer is obtained by covalent cross-linking of polyethylene glycol diacrylate, dopamine methacrylamide, double-bond modified silk fibroin and horseradish peroxidase, which achieves self-expanding and adhesion through the body fluid response shape memory characteristics.
It significantly reduces the mobility of the stent, improves the matching degree with human tissues, reduces the risk of patient discomfort and complications, and achieves biodegradability and efficient anti-shift function.
Smart Images

Figure CN119770755A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer materials, and specifically relates to a shape memory esophageal stent with anti-displacement function and a preparation method thereof. Background Art
[0002] Esophageal cancer is a common malignant tumor, which is often accompanied by esophageal stenosis during its development, seriously affecting the patient's nutritional intake and quality of life. At present, esophageal stent implantation is an effective means of treating esophageal stenosis. The stent is inserted into the stricture to restore the patency of the esophagus. The shape memory nickel-titanium alloy stents widely used in clinical practice utilize their shape memory effect. They are easy to transport at low temperatures and automatically unfold at body temperature to provide the necessary mechanical support for the esophagus. However, there are several technical bottlenecks in the existing nickel-titanium alloy stents. First, the material has poor biodegradability, which is not conducive to the natural absorption of the stent after short-term treatment, and increases the foreign body reaction in the patient's body. In addition, the high rigidity of nickel-titanium alloys does not match the mechanical properties of human tissues, which may cause patient discomfort and tissue damage.
[0003] In response to the above problems, the use of soft and degradable polymer materials to prepare esophageal stents provides a potential solution. The biocompatibility and degradation of polymer stents are better than those of metal stents, but their radial support force is relatively weak, resulting in a high displacement rate during application, which seriously limits their clinical application. At present, the main research direction for reducing the displacement rate is to enhance the interaction force between the stent and the esophageal tissue through physical structure design. However, due to the complexity of the peristalsis of the esophageal cavity, the anti-displacement effect of this type of design is limited and it is difficult to meet clinical needs.
[0004] In view of the limitations of existing technologies, this field urgently needs to develop a new type of esophageal stent. The stent material should have the following characteristics: biodegradability, high anti-displacement ability, mechanical behavior matching human tissue while providing effective support for the esophagus, and reliable deployment ability in the human environment. The development of this esophageal stent will significantly improve the clinical treatment effect of esophageal stents and reduce patients' pain and complication risks. Summary of the invention
[0005] In order to solve the deficiencies of the prior art, the present invention provides a shape memory esophageal stent with anti-displacement function and a preparation method thereof
[0006] The technical solution adopted by the present invention is:
[0007] 1. A shape memory esophageal stent with anti-displacement function
[0008] The shape memory esophageal stent with anti-displacement function has a double-layer structure, including a support layer and a tissue adhesion functional layer. The support layer provides the material with high-strength mechanical properties and is used to lock the permanent deformation of the material. The tissue adhesion functional layer has an interpenetrating porous structure, which can provide the material with tissue adhesion and mechanical properties matching the tissue, and is used to lock and release the temporary deformation of the stent material.
[0009] The shape memory esophageal stent with anti-displacement function has body fluid response shape memory characteristics, tissue adhesion, high modulus and mechanical behavior matching human tissue.
[0010] The support layer is constructed by a functionalized three-arm polylactic acid skeleton through catechol-metal ion coordination cross-linking.
[0011] The tissue adhesion functional layer is obtained by covalently cross-linking polyethylene glycol diacrylate, dopamine methacrylamide and double-bond modified silk fibroin.
[0012] The tissue adhesion functional layer also contains horseradish peroxidase.
[0013] The support layer and the tissue functional layer are connected to each other through the coordination effect of catechol-metal ions.
[0014] 2. A method for preparing a shape memory esophageal stent with anti-displacement function
[0015] The shape memory esophageal stent with anti-displacement function is prepared by the following method:
[0016] 1) By weight, 10 to 150 parts of functionalized three-arm polylactic acid are dissolved in dichloromethane, and then a methanol solution containing 0.05 to 2 parts of a metal salt and 0.1 to 5 parts of triethylamine are added in sequence during stirring to obtain a precursor solution of a support layer.
[0017] 2) pouring the precursor solution of the support layer onto the bottom layer of the rectangular mold, and allowing the dichloromethane solvent to evaporate completely at room temperature;
[0018] 3) dissolving 15 to 90 parts by mass of polyethylene glycol diacrylate, 1 to 15 parts by mass of dopamine methacrylamide, 10 to 85 parts by mass of double-bond-modified silk fibroin, 0.05 to 1 part by mass of horseradish peroxidase, and 0.2 to 2 parts by mass of a photoinitiator in water to obtain a precursor solution of a tissue adhesion functional layer;
[0019] 4) pouring the precursor solution of the tissue adhesion functional layer onto the surface of the support layer in the mold, leaving it to stand for 5 to 30 minutes, and then initiating a photocrosslinking reaction under ultraviolet light to obtain a gel-like tissue adhesion functional layer;
[0020] 5) freezing the mold in liquid nitrogen, and then completely freeze-drying it in a freeze dryer, and obtaining a dry polymer material with a double-layer structure after demoulding;
[0021] 6) The obtained polymer material is heated to 110° C. and then deformed to make the polymer into the size and shape of the desired stent, and ensure that the tissue adhesion layer is located on the outer surface of the esophageal stent. Subsequently, the esophageal stent with anti-displacement function is obtained by heat treatment at 120 to 140° C. for 1 to 4 hours.
[0022] In the step 1), the number average molecular weight of the functionalized three-arm polylactic acid is 8000-120000, and the metal salt is one or more of zinc chloride, ferric chloride, calcium chloride and cupric chloride.
[0023] In the step 3), the number average molecular weight of polyethylene glycol diacrylate is 4000-10000, the grafting rate of acrylate groups on the double bond modified silk fibroin is 2-15% in terms of mole percentage, and the photoinitiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.
[0024] 3. Application of shape memory esophageal stent with anti-displacement function in esophageal support.
[0025] 4. The application method of the shape memory esophageal stent with anti-displacement function in esophageal support is carried out through the following steps:
[0026] Step 1: heating the shape memory esophageal stent with anti-displacement function prepared according to the required size and shape to a temperature higher than the melting point of the tissue adhesion layer in the esophageal stent but lower than the glass transition temperature of the support layer, and then curling and compressing the esophageal stent to obtain a compressed shape memory esophageal stent with anti-displacement function; the compression reduces the radial size of the stent, which facilitates the transmission of the stent in the esophagus;
[0027] Step 2: Cooling the compressed shape memory esophageal stent with anti-displacement function to 0°C to fix the temporary shape of the compressed esophageal stent, thereby obtaining a shape memory esophageal stent with anti-displacement function with a fixed temporary shape.
[0028] Step 3: After the shape memory esophageal stent with a fixed temporary shape is delivered to the esophageal stenosis site, the tissue adhesion layer on the outer layer of the esophageal stent will quickly absorb the body fluid in the esophageal tissue due to its porous structure, and the shape will be restored based on the body fluid response, thereby realizing the self-expansion of the esophageal stent;
[0029] Step 4: After the esophageal stent spontaneously expands, it will continue to absorb body fluids in the esophageal tissue within its saturated swelling range and cause the esophageal stent to fully recover to its initial expanded state, thereby achieving mechanical support for the esophageal stenosis.
[0030] Step 5: The horseradish peroxidase in the tissue adhesion functional layer will catalyze the decomposition of high-concentration hydrogen peroxide in the tumor tissue, thereby oxidizing some of the catechol groups in the tissue adhesion functional layer into quinone structures. The oxidized catechol groups will react with polar groups such as amino, thiol, and nitro groups on the surface of the tumor tissue through Michael addition reactions to generate covalent bonds, and ultimately the anti-displacement function of the esophageal stent is achieved through the chemical and physical adhesion of the tissue adhesion functional layer to the esophagus.
[0031] The innovation of the present invention is:
[0032] The polymer stent is a double-layer structure, including a degradable support layer and a tissue adhesion functional layer. The support layer is constructed with a functionalized three-arm polylactic acid as the skeleton, and is obtained by coordination and cross-linking of the end-group-modified catechol groups with metal ions. The glass transition temperature of polylactic acid is higher than the body temperature, which ensures that the support layer maintains high mechanical strength during application. The three-arm structure provides appropriate chemical cross-linking points for the polymer network, and the coordination of catechol with metal ions further enhances the toughness of the support layer. This enables the support layer to effectively resist the radial pressure of the esophagus and provide favorable support for the esophageal stenosis. In addition, the support layer can be used to lock the permanent deformation of the esophageal stent and provide a driving force for the stent to recover its shape in response to stimulation.
[0033] The tissue adhesion functional layer of the polymer stent has an interpenetrating porous structure and tissue adhesion function. The interpenetrating porous structure is conducive to the rapid absorption of body fluids in the esophageal tissue during application, so that the tissue adhesion functional layer softens and swells rapidly. At the same time, the water in the body fluid destroys the crystalline phase of the polyethylene glycol segment in the tissue adhesion layer. The above process significantly reduces the mechanical strength of the tissue adhesion functional layer, so that the esophageal stent recovers its shape and self-expands under the drive of the support layer. After the esophageal stent self-expands, it will produce effective adhesion with the relatively dry esophageal tissue. Its adhesion mechanism includes chemical and physical effects. The chemical effect comes from the oxidation of catechol in the presence of horseradish peroxidase and the Michael addition reaction with the polar groups in the esophageal tissue to form a covalent bond adhesion. The physical effect mainly comes from the effective hydrogen bonding between the polar groups such as catechol, carboxyl, and amino in the tissue adhesion layer and the esophageal tissue. The chemical and physical adhesion of the tissue adhesion functional layer can effectively lock the stent material in the target site through the tissue adhesion functional layer, significantly improving its anti-displacement ability.
[0034] The beneficial effects of the present invention are as follows:
[0035] 1. The shape memory polymer esophageal stent provided by the present invention adopts a double-layer structure design including a support layer and a tissue adhesion functional layer. While meeting the high support performance required for the esophageal stent, it also has a good match with the mechanical behavior of human tissue, which will significantly reduce the discomfort and complications caused to patients by the material during application.
[0036] 2. The shape memory polymer esophageal stent provided by the present invention utilizes a combination of chemical and physical adhesion mechanisms to achieve efficient adhesion of the material to human esophageal tissue during application. In addition, the porous and soft tissue adhesion functional layer has good compliance to the peristalsis of the esophageal tissue, which not only further effectively reduces the migration of the stent, but also reduces the discomfort of the patient.
[0037] 3. The shape memory polymer esophageal stent provided by the present invention can achieve self-expansion and deployment at the lesion site through the shape memory property of body fluid response during use, which is beneficial to the implantation operation.
[0038] 4. The shape memory polymer esophageal stent provided by the present invention is biodegradable and can be self-degraded in the human body, reducing the surgical pain of the patient. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 is the chemical structural formula of the functionalized three-arm polylactic acid used in Example 1.
[0040] Figure 2 Schematic diagram of the double-layer structure of the polymer material synthesized in Example 1.
[0041] Figure 3 This is a schematic diagram of the process of preparing a shape memory esophageal stent with anti-displacement function using the synthesized double-layer polymer material in Example 1.
[0042] Figure 4 This is a schematic diagram of temporary shape fixation and implantation of the esophageal stent with anti-displacement function in Example 1. DETAILED DESCRIPTION
[0043] The specific implementation is described in detail below in conjunction with the accompanying drawings, but it should be understood that the protection scope of the present invention is not limited by the specific implementation. The raw materials and reagents used in the examples are all commercially available unless otherwise specified.
[0044] Embodiments of the present invention are as follows:
[0045] Example 1
[0046] 961.6 mg of functionalized three-arm polylactic acid was dissolved in 10 ml of dichloromethane, and 0.2 ml of a methanol solution containing 8.4 mg of zinc chloride and 17.1 mg of triethylamine were added during stirring to obtain a precursor solution of the support layer; the precursor solution of the support layer was poured into a flat rectangular mold, and the dichloromethane was naturally evaporated completely at room temperature; then 472.4 mg of polyethylene glycol diacrylate, 51.3 mg of dopamine methacrylamide, 261.5 mg of double-bond modified silk fibroin, 2.6 mg of horseradish peroxidase, and 6.2 mg of 2-Hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone was dissolved in water to obtain a precursor solution of the tissue adhesion functional layer, which was poured onto the surface of the support layer in the mold, and then allowed to stand for 15 minutes before initiating a cross-linking reaction under ultraviolet light; the mold was placed in liquid nitrogen for 1 minute, and then placed in a freeze dryer for complete freeze drying, and a dry polymer material with a double-layer structure was obtained after demolding; the tensile strength of the obtained polymer material was 46.4±0.24MPa, and the adhesion strength was 19.6kPa. The Young's modulus of the support layer was 1614.6±52.4MPa, and the Young's modulus of the tissue adhesion functional layer was 0.31±0.06MPa. When the obtained polymer material was heated to 110°C, it was deformed according to the size and shape of the required esophageal stent, and the tissue adhesion layer was ensured to be located on the outer surface of the esophageal stent, and then heat treated at 130°C for 2h to obtain a shape memory esophageal stent with the required size and shape and anti-displacement function.
[0047] In this embodiment, the functionalized three-arm polylactic acid used is terminated with a catechol group, and its chemical structure is as follows: Figure 1 As shown, its number average molecular weight is 26400 and its glass transition temperature is 64.2° C. The grafting rate of the acrylate group of the double bond modified silk fibroin is 6.1%.
[0048] like Figure 2 , which is a schematic diagram of the double-layer structure of the polymer material synthesized in this embodiment. As shown in the figure, the support layer is a polymer layer with a dense structure, and the tissue adhesion functional layer is a polymer layer with an interpenetrating porous structure, and its interpenetrating porous structure is caused by the sublimation of ice crystal particles in the polymer network during freeze-drying.
[0049] like Figure 3 As shown in the figure, it is a schematic diagram of the process of preparing a shape memory esophageal stent with anti-displacement function using the synthesized double-layer polymer material in this embodiment. As can be seen from the figure, the polymer material with a planar rectangular shape can obtain a given cylindrical stent shape after deformation and heat treatment at 130°C for 2h. The design and preparation of the stent in shape and size can be carried out according to different requirements.
[0050] like Figure 4As shown, it is a schematic diagram of temporary shape fixation and implantation of the esophageal stent with anti-displacement function in this embodiment. As can be seen from the figure, the esophageal stent can be fixed in a compressed temporary state by sequentially performing compression deformation, heat treatment at 45°C for 10 minutes, and cooling to room temperature. After the stent is implanted in the esophageal stenosis, the tissue adhesion functional layer on the outer surface of the stent will quickly absorb the body fluid in the esophageal tissue area, triggering shape recovery, and changing from a contracted state to a cylindrical expanded state, thereby achieving support for the esophageal stenosis.
[0051] Example 2
[0052] 1498.6 mg of functionalized three-arm polylactic acid was dissolved in 10 ml of dichloromethane, and 0.2 ml of methanol solution containing 19.6 mg of copper chloride and 49.1 mg of triethylamine were added during stirring to obtain a precursor solution of the support layer; the obtained precursor solution of the support layer was poured into a flat rectangular mold, and the dichloromethane was naturally evaporated completely at room temperature; then 895.5 mg of polyethylene glycol diacrylate, 147.2 mg of dopamine methacrylamide, 102.4 mg of double-bond modified silk protein with a grafting rate of 14.6% of acrylate groups, 9.7 mg of horseradish peroxidase, and 19.2 mg of 2-Hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone was dissolved in water to obtain a precursor solution of the tissue adhesion functional layer, which was poured onto the surface of the support layer in the mold, and then allowed to stand for 5 minutes before initiating a cross-linking reaction under ultraviolet light; the mold was placed in liquid nitrogen for 1 minute, and then placed in a freeze dryer for complete freeze drying, and a dry polymer material with a double-layer structure was obtained after demolding; the tensile strength of the obtained polymer material was 52.3±0.32MPa, and the adhesion strength was 17.4kPa. The Young's modulus of the support layer was 1741.2±69.3MPa, and the Young's modulus of the tissue adhesion functional layer was 0.27±0.05MPa. When the obtained polymer material was heated to 110°C and deformed according to the size and shape of the required esophageal stent, and the tissue adhesion layer was ensured to be located on the outer surface of the esophageal stent, and then heat treated at 140°C for 1h, a shape memory esophageal stent with anti-displacement function of the required size and shape was obtained.
[0053] Example 3
[0054] 100.6 mg of functionalized three-arm polylactic acid was dissolved in 10 ml of dichloromethane, and 0.2 ml of methanol solution containing 0.56 mg of calcium chloride and 1.13 mg of triethylamine were added during stirring to obtain a precursor solution of the support layer; the obtained precursor solution of the support layer was poured into a flat rectangular mold, and the dichloromethane was naturally evaporated completely at room temperature; then 151.2 mg of polyethylene glycol diacrylate, 10.7 mg of dopamine methacrylamide, 848.4 mg of modified silk protein with a grafting rate of 2.1% of acrylate groups, 0.55 mg of horseradish peroxidase, and 2.6 mg of 2-Hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone was dissolved in water to obtain a precursor solution of the tissue adhesion functional layer, which was poured onto the surface of the support layer in the mold, and then allowed to stand for 30 minutes before initiating a cross-linking reaction under ultraviolet light; the mold was placed in liquid nitrogen for 1 minute, and then placed in a freeze dryer for complete freeze drying, and a dry polymer material with a double-layer structure was obtained after demolding; the tensile strength of the obtained polymer material was 21.6±0.11MPa, and the adhesion strength was 26.2kPa. The Young's modulus of the support layer was 824.2±25.4MPa, and the Young's modulus of the tissue adhesion functional layer was 0.33±0.06MPa. When the obtained polymer material was heated to 110°C and deformed according to the size and shape of the required esophageal stent, and the tissue adhesion layer was ensured to be located on the outer surface of the esophageal stent, and then heat treated at 120°C for 4h, a shape memory esophageal stent with anti-displacement function of the required size and shape was obtained.
[0055] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. A shape memory esophageal stent with anti-displacement function, characterized in that: The shape memory esophageal stent with anti-displacement function has a double-layer structure, including a support layer and a tissue adhesion functional layer. The support layer provides the material with high-strength mechanical properties and is used to lock the permanent deformation of the material. The tissue adhesion functional layer has an interpenetrating porous structure, which can provide the material with tissue adhesion and mechanical properties matching the tissue, and is used to lock and release the temporary deformation of the stent material.
2. The shape memory esophageal stent with anti-displacement function according to claim 1, characterized in that: It has fluid-responsive shape memory properties, tissue adhesion, high modulus, and mechanical behavior that matches that of human tissue.
3. The shape memory esophageal stent with anti-displacement function according to claim 1, characterized in that: The support layer is constructed by using functionalized three-arm polylactic acid as the skeleton and through catechol-metal ion coordination cross-linking.
4. The shape memory esophageal stent with anti-displacement function according to claim 1, characterized in that: The tissue adhesion functional layer is obtained by covalently cross-linking polyethylene glycol diacrylate, dopamine methacrylamide and double-bond modified silk fibroin.
5. The shape memory esophageal stent with anti-displacement function according to claim 1, characterized in that: The tissue adhesion functional layer contains horseradish peroxidase.
6. The shape memory esophageal stent with anti-displacement function according to claim 1, characterized in that: The support layer and the tissue functional layer are connected to each other through the coordination effect of catechol-metal ions.
7. The shape memory esophageal stent with anti-displacement function according to claims 1-6, characterized in that: The shape memory esophageal stent with anti-displacement function is prepared by the following method: 1) By weight, 10 to 150 parts of functionalized three-arm polylactic acid are dissolved in dichloromethane, and then a methanol solution containing 0.05 to 2 parts of a metal salt and 0.1 to 5 parts of triethylamine are added in sequence during stirring to obtain a precursor solution of a support layer. 2) pouring the precursor solution of the support layer onto the bottom layer of the mold, and allowing the dichloromethane solvent to evaporate completely at room temperature; 3) dissolving 15 to 90 parts by mass of polyethylene glycol diacrylate, 1 to 15 parts by mass of dopamine methacrylamide, 10 to 85 parts by mass of double-bond-modified silk fibroin, 0.05 to 1 part by mass of horseradish peroxidase, and 0.2 to 2 parts by mass of a photoinitiator in water to obtain a precursor solution of a tissue adhesion functional layer; 4) pouring the precursor solution of the tissue adhesion functional layer onto the surface of the support layer in the mold, leaving it to stand for 5 to 30 minutes, and then initiating a photocrosslinking reaction under ultraviolet light to obtain a gel-like tissue adhesion functional layer; 5) freezing the mold in liquid nitrogen, and then completely freeze-drying it in a freeze dryer, and obtaining a dry polymer material with a double-layer structure after demoulding; 6) The obtained polymer material is heated to 110° C. and then deformed to make the polymer into the size and shape of the desired stent, and ensure that the tissue adhesion layer is located on the outer surface of the esophageal stent. Subsequently, the esophageal stent with anti-displacement function is obtained by heat treatment at 120 to 140° C. for 1 to 4 hours.
8. The method for preparing a shape memory esophageal stent with anti-displacement function according to claim 7, characterized in that: The number average molecular weight of the functionalized three-arm polylactic acid in step 1) is 8000-120000, and the metal salt is one or more of zinc chloride, ferric chloride, calcium chloride and copper chloride.
9. The method for preparing a shape memory esophageal stent with anti-displacement function according to claim 7, characterized in that: The number average molecular weight of the polyethylene glycol diacrylate in step 3) is 4000-10000, the grafting rate of the acrylate groups on the double bond-modified silk fibroin is 2-15% in terms of mole percentage, and the photoinitiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.